Gender and Semantic Interpretation - Z Zainurrahman (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2019)
The views that gender and language are related each other has been reviewed from at least two different disciplines: sociolinguistics and psychology. From the first discipline, it has been concluded that gender and language has no natural relationship for it is cultural values that shape genderlect. From the second discipline, it has been concluded that gender and language has natural relationship for different gender has different brain architecture. However, still, these views tend to focus more on the language production. Viewed from language comprehension, specified to semantic interpretation, this research involved 60 participants (30 males and 30 females) randomly taken from various affiliations with age ranged from 18-32 years old. 30 questions concerning semantic interpretation which are divided into entailment, presupposition, and basic syllogism are given. The result confirms various theories about ‘gendered-brain’ especially lateralization theory. This research has concluded that there is a natural relationship between gender and semantic interpretation.